Interpretation of the Symbolic Meaning in the Sri Kayun Traditional Dance in Kulon Progo Regency - Fadila Ramadante; Siany Indria Liestyasari (Warisan: Journal of History and Cultural Heritage, 2026)
This study examines the Sri Kayun dance, which has served as the official welcoming dance of Kulon Progo Regency since 2022. This research aims to identify, describe, and interpret the symbolic meanings embedded in the movements of the Sri Kayun dance, as well as the cultural values that underlie it. The study is guided by a semiotic approach to explain how symbolic meanings are constructed and represented within the performance. The research employs a descriptive qualitative method using a case study approach. Data were collected through observation, interviews, literature reviews, and documentation. The findings reveal that the name "Sri Kayun" embodies a philosophical concept of inner and outer beauty that functions not merely as an aesthetic marker but as a normative cultural ideal for the community. The dance movements illustrate respect, humility, social harmony, and cooperation. The study argues that the Sri Kayun dance operates as a symbolic system through which cultural identity and social values are continuously constructed and communicated. Symbolic meanings are embedded in every element of the performance, positioning it as a cultural text that requires interpretation.